Use of Facebook Social Media as Product Marketing Media - Muhammad Anshari Hutasuhut; Siti Hazrah; Vania Sally Nabila; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
Everyone needs information to support their activities, so try to access information as quickly as possible. To introduce products or services that will be sold, companies or small and medium-sized businesses need promotions, and the pattern in the field of business through Facebook or through a web-based shop is very encouraging. The creator utilizes an enlightening subjective examination approach where the information gathered is predominantly as words and sentences, or pictures that have more significance than numbers or frequencies. Execution of the utilization of Facebook web- based media incorporates building data methodologies, planning advancements and building networks by using gatherings and fanspages.